Effects of Biochar, Lime, and Compost Applications on Soil Physicochemical Properties and Yield of Pomelo (Citrus grandis Osbeck) in Alluvial Soil of the Mekong Delta - Le Van Dang; Ngo Phuong Ngoc; Ngo Ngoc Hung (Applied and Environmental Soil Science)
Soil acidity is an important factor affecting crop productivity in the tropics. The soil of the Vietnamese Mekong Delta has high acidity, deficient levels of exchangeable bases, and low fertility. This study aimed to evaluate soil amendments’ role in improving soil fertility, soil acidity, and pomelo yield cultivated in raised beds. The field trial was carried out in Hau Giang Province consecutively over 3 years from 2018 to 2020. Four treatments were used, namely control, biochar (5 ton·ha−1·year−1), lime (2 ton·ha−1·year−1), and compost (5 ton·ha−1·year−1). All treatments applied the same amount of NPK fertilizers at rates of 400 kg·N, 300 kg·P2O5, and 400 kg·K2O·ha−1·year−1. Physicochemical properties of the topsoil (0–20 cm) and subsoil (20–40 cm) and fruit yield were investigated. The results showed that biochar or compost application increased soil pH, soil organic matter (SOM), and exchangeable cations and decreased soil bulk density (BD), improving soil fertility and fruit yield in the raised beds. Applications of biochar or compost resulted in about 1.5-fold higher fruit yield than that of chemical fertilizer alone. The average profit increased to USD 1,672 ha−1 after applying biochar and compost in the three-year experiments. Biochar and compost amendments have a positive effect on reducing soil acidity and soil BD, elevating SOM, supplying available Ca2+ and Mg2+, improving soil fertility, enhancing fruit yield, and increasing profit.